The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/0001-3765202120190478
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil of Mentha suaveolens Ehrh., composition and antibacterial activity against bacterial fish pathogens

Abstract: In this study, it was determinated the essential oil of cultivated apple mint, Mentha suaveolens Ehrh. composition and in vitro antibacterial activity of against 11 fi sh pathogen bacteria including Gram-positive (Staphylococcus warneri, Staphylococcus sp., Lactococcus garvieae, Vagococus salmoninarum) and Gram-negative (Aeromonas hydrophila, Aeromonas sobria Aeromonas cavieae, Vibrio anguillarum, Pseudomonas aeroginosa, Yersinia ruckeri, Edwardsiella tarda) by using agar diffusion assay. The main component of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Essential oil of Mentha suaveolens Ehrh. were studied by Metin and co-workers [18] to determine the in vitro antibacterial activity against 11 fish pathogen bacteria including Gram-positive (Staphylococcus warneri, Staphylococcus sp., Lactococcus garvieae, Vagococus salmoninarum) and Gram-negative (Aeromonas hydrophila, Aeromonas sobria, Aeromonas cavieae, Vibrio anguillarum, Pseudomonas aeroginosa, Yersinia ruckeri, Edwardsiella tarda) by using agar diffusion assay. As a result of the research, it was revealed that essential oil exhibited strong inhibitory activity such as inhibition zone sizes: 30-50 mm at 250-1000 µL mL -1 concentrations against V. anguillarum; 16-20 mm at 31.25-125 µL mL -1 concentrations against P. aeroginosa; 15-18 mm at 500-1000 µL mL -1 concentrations against A. sobria [18].…”
Section: Resultsmentioning
confidence: 99%
“…Essential oil of Mentha suaveolens Ehrh. were studied by Metin and co-workers [18] to determine the in vitro antibacterial activity against 11 fish pathogen bacteria including Gram-positive (Staphylococcus warneri, Staphylococcus sp., Lactococcus garvieae, Vagococus salmoninarum) and Gram-negative (Aeromonas hydrophila, Aeromonas sobria, Aeromonas cavieae, Vibrio anguillarum, Pseudomonas aeroginosa, Yersinia ruckeri, Edwardsiella tarda) by using agar diffusion assay. As a result of the research, it was revealed that essential oil exhibited strong inhibitory activity such as inhibition zone sizes: 30-50 mm at 250-1000 µL mL -1 concentrations against V. anguillarum; 16-20 mm at 31.25-125 µL mL -1 concentrations against P. aeroginosa; 15-18 mm at 500-1000 µL mL -1 concentrations against A. sobria [18].…”
Section: Resultsmentioning
confidence: 99%
“…This may be by disrupting the cell wall, membrane permeabilization, targeting drug efflux pumps, targeting quorum sensing, biofilms, and R-plasmids (23). Many studies have reported that EOs are more effective against gram-positive than gram-negative bacteria, possibly due to the different compositions in the cell walls, as gram-negative bacteria possess a rigid outer membrane rich in lipopolysaccharides limiting the diffusion of hydrophobic compounds through it, making these bacteria less susceptible (24,25). In our study, the EOs were effective on both gram-positive and gram-negative bacterial pathogens, as shown clearly in the results of the microdilution assay.…”
Section: Discussionmentioning
confidence: 99%
“…Leukogram of diseased calves revealed significant increase in TLC, neutrophil, monocyte and eosinophil but lymphocyte count showed a significant decreased compared to control group. The bacterial infection leads to inflammation and suppuration, therefore leukogram response to the inflammatory disease (Coles, 1986) (Metin et al, 2021). It is noted that levamisole has a hormone-like effect due to the increase in the amount of intracellular cGMP and serum factors responsible for leukocyte activation in lymphocytes exposed to levamisole (Kızıltepe, 2018).…”
Section: Et Al (2022)mentioning
confidence: 99%